High Origin of Radial Arteries: A Report of Two Rare Cases. (2010) - Zhan, Dong; Zhao, Yi; Sun, Jun; Ling, Eng-Ang; Yip, George W.
Abstract : Variations in the arterial supply of the upper limb are relatively common, with reported prevalence rates ranging from 11 to 24.4%. Of these, the most commonly encountered variation in the arm is a high origin of the radial artery. However, after consecutively dissecting and examining 600 Singaporean Chinese cadavers (1, 200 upper limbs), we found only two cases of this. In both cases, the brachioradial artery originated from the upper one-third of the brachial artery and continued distally as the radial artery in the forearm. The local prevalence of 0.33% of this variation is significantly lower compared against populations from other geographical regions. Although rare, recognition of the variation is of fundamental importance to clinical practice.